Comparison and Evaluation of the Mental Health and Life Satisfaction between Male and Female Employees of Counseling Clinics in Yazd City - Ali Jafari Nodoushan; Hasan Zare; Reza Bidoki; Hamideh Radpour (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: This study aimed to compare and evaluate the mental health and life satisfaction of male and female employees of counseling clinics in Yazd city. Methods: This causal- comparative study was conducted on 100 employees of counseling clinics in Yazd city including 50 women and 50 men. These participants were selected through available sampling and were required to complete Diner's two questionnaires of mental health and scale of life satisfaction. The data were then analyzed by SPSS20 software. Results: The results showed that there is no significant difference between mental health levels of male and female employees. Moreover, there was no significant difference between male and female employees' life satisfaction. However, there was a significant positive correlation between mental health and life satisfaction among men and women. Conclusion: Since this study included people with bachelor degree and higher, conducting more widespread studies with random sampling are recommended to reduce the error variance.